Code CODE-SWITCHING IN BILINGUAL EDUCATION: COGNITIVE AND SOCIAL IMPLICATIONS - Al-musthofa, Wardaniatul Firdausia; D'Angelo, James F. (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2024)
This research focuses on the role of code-switching in bilingual education, examining the cognitive and social implications of the practice. Using a qualitative approach with a case study method, this research analyzes how code-switching affects students' comprehension and social interaction in the bilingual classroom. Data were collected through semi-structured interviews, participatory observation, and document analysis in several bilingual schools. The results show that code-switching plays an important role in helping students understand complex material and in strengthening their social identity. Cognitively, code-switching allows students to utilize their first language to understand difficult concepts, while socially, the practice reinforces inclusivity and positive dynamics in the classroom. The implications of the findings confirm that code-switching is an effective pedagogical strategy and not simply a communication tool. The recommendations of this study encourage educators and policy makers to integrate code-switching as an integral part of teaching strategies in bilingual education, to support more inclusive and effective learning.